Analisis Pengaruh Stress Kerja, Disiplin Kerja dan Konflik Kerja Terhadap Kinerja Pegawai - Alfurqon, Nicko Falih; Rahardjo, Budi (Universitas Nusa Putra, 2020)
One of the factors that can increase employee productivity, i.e. employee performance. Good employee performance determines the achievement of the agency's productivity. Officers with difficulty adjusting can be the stressor that will impede the process of working. The stress that negatively impacts is called distress and stress that is positively impactful is called eustress. A company needs to conduct a performance assessment on its employees. The Data is a crossection with a nominal scale, essentially using a Likert scale. Employee performance is the result employees work with following their instructions, direction, compensation, and ability. Partial hypothesis test (test-F) significance that variable Stress work discipline variables and working conflicts have a significant effect on employee performance in the economic part of Magelang Regency which stated that there is an influence on employee performance. Based on the results of data analysis in this study came the conclusion that work stress, work discipline, and work conflict jointly (simultaneous) affects employees ' performance in the economic part of Magelang regency.